Dealership E-Commerce Development Project (Configurable Web-Site Template - Webecommerce) / Ong Yen Horng - Ong, Yen Horng (2002)
This project is to develop a web-based configurable template for e-commerce capabilities. This web-based template is used to generate web-based e-commerce package that fulfill the requirements of the dealers involved. This template can later be edited and updated as requirements change and evolve. Changes will be reflected in the web site created. This project is called WebEcommerce. Overall, WebEcommerce consists 3 major sections. First, WebEcommerce Template Setup that is a password protected web-based application that running in the dealer's server. With just a few steps, dealer can setup their own web site. Second, WebEcomrnerce Template Maintenance that also is a password protected web-based application that running in the dealer's server. It only allows for registered dealer that having their ID and password to update or modify the information in the created web site. Lastly, WebEcommerce Web Site that purposely tailored to dealer requirement. This web site will use by dealer for their daily transaction that interact with customer like e-shopping, e-ordering and e-payment. Based on the research, there is non of the company in Malaysia provided e-commerce template like propose in this thesis report. But it is very popular in oversea In order to improve the existing system from oversea company, a lot of survey and analysis have been done especially on the layout and flexibility of the template that already exist. Besides, research for software and tools that used to develop this project have been done, then will just decide the most suitable tools to use in this project. After the literature review, will forward to analysis of the requiremenst. DFD that related to this project will be work out. The next section of this report is system design. Some of the example of the system design will be included in this project. The following section is system implementation that include techniques and approach that used to build the system and describe in more details manner. The last section will be the system testing. This section includes the testing process and approach used to test the system. This package is tailor to dealer so called Dealership E-Commerce Development Project. With joining this project will not just enhance relationships with dealers and customers, but also giving the opportunity to help the dealer's business fly!